Trace elements microanalysis of metal oxides in deposit formed on combustion chamber surface of landfill gas engine using focused ion beam/scanning electron microscopy technique. (May 2021) - Östürk, Özge; Sevimoğlu, Orhan
Graphical abstract: SEM images of deposits lateral surfaces, a) top and bottom surface of photograph image. Highlights: The elemental distributions of the deposit surfaces were studied by SEM-FIB-EDS. The morphology of the deposit bottom, top and lateral surfaces were studied by SEM. Ca, S, Si are the major elements in the formed deposits originated from impurities. Antimony is detected in the deposit as hazardous element. WDXRF analysis determined the elements in the deposit bulk. Abstract: The aim of this study is to investigate the deposit formed on the inner surface of the combustion chamber of the landfill gas engine based on its morphological structure and elemental composition. The responsible elements for deposit formation that affects the engine's operating performance were determined on the differences of the microstructural and chemical composition of deposits using Scanning Electron Microscope with Energy Dispersive Spectrometry and Focused Ion Beam. The Oxygen element of metal oxides made up about half of the deposit mass. Nitrogen was also detected in the deposit by FIB analysis. The amount of elements on the bottom surface to the engine part were ordered Si > S > Ca > Al > Mg > Sn > Sb, on the other side, the elements on the top surface of the accumulated deposit were Ca > S > Si > Sn. The elemental distribution of the top surface was overlapped with both results of the elemental distribution of the longitudinal lateral section area and the cross-sectional area. The amount of Si increased from the top surface to the bottom surface, and the amount of Ca and S decreased. These findings revealed that Si, S, and Ca have various roles in deposit formation from start to end. WDXRF Spectrometer analysis confirmed that Si, S, and Ca are the major elements with approximately half of the deposit is made up of oxygen element. The detected Sb and Sn made the deposits to be considered as hazardous material in the disposal process.